2021
DOI: 10.1007/s10508-021-01920-1
|View full text |Cite
|
Sign up to set email alerts
|

Slutpage Use Among U.S. College Students: The Secret and Social Platforms of Image-Based Sexual Abuse

Abstract: The phenomenon of "slutpages," tied to high schools, fraternities, and the military, used to post, share, and comment on nude and semi-nude images of women, has emerged in mass media. To our knowledge, this is the first study to empirically investigate slutpage use behaviors including: visiting slutpages, posting nude images/videos online without consent, and using a vault app to store/share nude images. We conducted a survey of undergraduate college students attending a large Midwestern university in the U.S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…However, the only empirical study regarding OIBEV to our knowledge (Maas et al, 2021), found that 30% of women also viewed "slutpages, " albeit less frequently than men (40%). Given that most OIBEVS almost exclusively depict women, and are predominantly designed for the male gaze, this gives rise to questions about why women would view such sites.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…However, the only empirical study regarding OIBEV to our knowledge (Maas et al, 2021), found that 30% of women also viewed "slutpages, " albeit less frequently than men (40%). Given that most OIBEVS almost exclusively depict women, and are predominantly designed for the male gaze, this gives rise to questions about why women would view such sites.…”
Section: Introductionmentioning
confidence: 79%
“…In the hierarchical regressions, the combined demographic variables did not explain large amounts of variance, with sexting-related variables offering more explanatory power for OIBEV behaviors. Although our sample was not restricted to college or tertiary students, higher OIBEV frequencies in the United States may reflect higher engagement in tertiary residential social societies (e.g., sororities, fraternities) which are more common in United States institutions, and are associated with higher levels of OIBEV use (Maas et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of “slutpages”, particularly in the USA, is an example of self-generated pornography where women are exposed to another form of pornography-inspired exploitative behaviour [ 86 ].…”
Section: Impacts On Behaviourmentioning
confidence: 99%